Relationship between precipitation cycles and floods in the northeast region of the province of La Pampa and west of Buenos Aires: (Ingeniería Agronómica) (Semiárida, 2023)
Flood events are recurrent in the Pampas region. In the western portion, called the Pampas semi-arid region (RSP), periods of excess water alternate with droughts of varying duration. Floods produce negative consequences on the quality of life of the population, infrastructure and agricultural production. To develop mitigation strategies for these effects, it is important to know the dynamics of water excess. In this study, the spatio-temporal pattern of flooded surfaces in the last 27 years was determined in an area of 29,728 km2 of the RSP. The flooded areas were delineated based on interpretation of images from the historical series of the LANDSAT mission using automatic digitization techniques. One high-quality image per year (
Keywords: precipitation